The Arabs and the Holocaust : the Arab-Israeli war of narratives - Achcar, Gilbert; Goshgarian, G. M. (London Saqi Books, 2011)
Considers conflicting Middle-East perspectives on the Holocaust, analyzing such topics as Arab responses to Nazism, the creation of Israel, and the destruction of Palestine.
Part I: The Time of the Shoah -- Arab Reactions to Nazism and Anti-Semitism, 1933-47 -- Part I. The Liberal Westernizers -- 2. The Marxists -- 3. The Nationalists -- 4. Reactionary and/or Fundamentalist Pan-Islamists -- Part II: The Time of Nakba -- Arab Attitudes to the Jews and the Holocaust from 1948 to the Present -- 5. The Nasser Years (1948-67) -- 6. The PLO Years (1967-88) -- 7. The Year of the Islamic Resistances (1988 to the Present) -- Conclusion: Stigmas and Stigmatization
Originally published in France by Actes Sud as Les arabes et la Shoah
Includes bibliographical references and index
Keywords: History; HOLOCAUST; PUBLIC OPINION; NATIONALISM; JEWS; ARABS